Oblique Sagittal Images Prevent Underestimation of the Neuroforaminal Stenosis Grade Caused by Disc Herniation in Cervical Spine MRI - Kintzelé, Laurent; Rehnitz, Christoph; Kauczor, Hans-Ulrich; Weber, Marc-André (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose To identify whether standard sagittal MRI images result in underestimation of the neuroforaminal stenosis grade compared to oblique sagittal MRI images in patients with cervical spine disc herniation.Materials and Methods 74 patients with a total of 104 cervical disc herniations compromising the corresponding nerve root were evaluated. Neuroforaminal stenosis grades were evaluated in standard and oblique sagittal images by one senior and one resident radiologist experienced in musculoskeletal imaging. Oblique images were angled 30° towards the standard sagittal plane. Neuroforaminal stenosis grades were classified from 0 (no stenosis) to 3 (high grade stenosis).Results Average neuroforaminal stenosis grades of both readers were significantly lower in standard compared to oblique sagittal images (p < 0.001). For 47.1 % of the cases, one or both readers reported a stenosis grade, which was at least 1 grade lower in standard compared to oblique sagittal images. There was also a significant difference when looking at patients who had neurological symptoms (p = 0.002) or underwent cervical spine surgery subsequently (p = 0.004). Interreader reliability, as measured by kappa value, and accordance rates were better for oblique sagittal images (0.94 vs. 0.88 and 99 % vs. 93 %).Conclusion Standard sagittal images tend to underestimate neuroforaminal stenosis grades compared to oblique sagittal images and are less reliable in the evaluation of disc herniations within the cervical spine MRI. In order to assess the potential therapeutic consequence, oblique images should therefore be considered as a valuable adjunct to the standard MRI protocol for patients with a radiculopathy.Key Points Citation Format
Keywords: oblique sagittal images; neuroforaminal stenosis; disc herniation; cervical spine; MR imaging